Engineering superhydrophobicity: a survey of coating techniques for silicone-based oil–water separation membranes - Shastri, Abhilasha; Gore, Prakash M.; Kandasubramanian, Balasubramanian (Environmental science and pollution research international, 2024)
Oil spills in the ocean and the release of contaminated wastewater from industries cause significant harm to the ecosystem and water sources. To tackle this environmental problem, oil–water mixture separation has been the subject of extensive research over the past few decades. Improving oil absorbents is crucial in removing organic contaminants from wastewater produced by industrial activities. To this end, there is an increasing need for materials that can efficiently and flexibly recover oils from contaminated ocean waters, industrial wastewater, and other sources. Silicones are often used for this purpose because of their exceptional mechanical and thermal durability, as well as their low toxicity. The materials produced from silicones, such as foam, sponge, or substrate, exhibit excellent oil-absorbing properties (maximum oil absorption range, 23.2–77 g/g) and outstanding compression cycles. This article review highlights the advancements in the manufacturing of silicone-based products that have been extensively researched for oil–water separation. Understanding the interdependencies that determine the structure, performance, and manufacturing strategy is essential to producing selective oil absorbents with more commercial potential in the future. Recycling of silicones has also become increasingly important as a goal for the circular economy. Graphical Abstract